Sharp Estimates of m-Linear p-Adic Hardy and Hardy-Littlewood-Pólya Operators - Qingyan Wu; Zunwei Fu (Journal of Applied Mathematics)
The sharp estimates of the m-linear p-adic Hardy and Hardy-Littlewood-Pólya operators on Lebesgue spaces with power weights are obtained in this paper.